(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The questions of supplying power to the region with remote consumers are considered. The model of integrated power supply is proposed. Mathematical dependences that allow accounting volumes of certain types energy resources consumption and forming rational energy balance of the region are formulated.